Influence of Magnetite Nanoparticles on the Dielectric Properties of Metal Oxide/Polymer Nanocomposites Based on Polypropylene - Maharramov, A. A.; Ramazanov, M. A.; Di Palma, Luca; Shirinova, H. A.; Hajiyeva, F. V. (Russian physics journal, 2018)
Structure and dielectric properties of polymer nanocomposites based on isotactic polypropylene and iron oxide (Fe 3 O 4 ) nanoparticles are studied. Distribution of magnetite nanoparticles in a polymer matrix was studied by scanning electron microscopy (SEM, Carl Zeiss). Dielectric properties of nanocomposites were examined by means of E7-21 impedance spectrometer in the frequency range of 10 2 –10 6 Hz and temperature interval of 298–433 K. The frequency and temperature dependences of the dielectric permittivity ε, as well as the temperature dependence of log (ρ) were constructed. It is shown that introduction of the magnetite (Fe 3 O 4 ) nanoparticles into a polypropylene matrix increases the dielectric permittivity of nanocomposites. An increase in the dielectric permittivity is explained by the increase in the polarization ability of nanocomposites. It is found that a decrease in the specific resistance with increasing temperature up to 318 K is associated with an increase in the ionic conductivity of nanocomposites. An increase in the resistance at temperatures higher than 358 K is due to the destruction of the crystalline phase of the polymer, as a result of which the distance between the Fe 3 O 4 nanoparticles increases.